Evaluation of Drug Management For Tuberculosis (TB) Program At Pharmaceutical Installation Public Health Department of North Sumatra Province - Sabri, April; S, Wiryanto M; M, Khairunnisa (Asian Journal of Pharmaceutical Research and Development, 2019)
Objective: Drug management consists of planning, storing and distribution. It is one of the important duty of Public Health Department of North Sumatra Province. Poor drug management will give a negative impact on service quality. This research aimed to evaluate the management of drug programs for tuberculosis (TB) in 2017, 2018 and 2019 in the Public Health Department of North Sumatra Province. The research was conducted in July - September 2019. Method: This research was descriptive with quantitative data obtained retrospectively and concurrently. Qualitative data were obtained through observations and interviews with informants. The data obtained were analyzed using indicators and compared with the results of the research. Result: The result of the research showed that planning, storing and distributing drug for the TB program in the Public Health Department of North Sumatra Province had not fully met the indicator standards. This was indicated by the 6 indicators which had not met the standard, that were the accuracy of planning; planning deviations; level of drug supply; percentage of expired drug; Inventory Turn Over Ratio (ITOR); the average time of drug vacancies and the percentage of dead drug stock and 3 indicators had met the standards, which were the percentage of expired drugs, the structuring system of drugs and the matching of the number of real goods with stock. Conclusion: the conclusion of this research is drug planning of Public Health Department of North Sumatra Province uses consumption method of previous period. Storage of drugs uses the FIFO/FEFO system. Drug distribution in the North Sumatra Provincial Health Office is based on requests from the District/City.